2002
DOI: 10.1108/00251740210422866
|View full text |Cite
|
Sign up to set email alerts
|

The mutability of charisma in leadership research

Abstract: This article reveals the mutability of charisma by tracing changes in the conceptualization of charisma throughout the history of leadership research. Religious, societal, and organizational phases in the conceptualization of charisma are identified. The mutability of charisma has extended charismatic leadership theory from the domain of theology to multiple facets of the organizational sciences. Shifting conceptualizations of charisma that emphasize different elements have facilitated the study of leader trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…Inconsistent findings and methodological problems resulting in increasing dissatisfaction with trait, behavioral, and contingency based leadership research had The case of Jordanian schools set the stage for a paradigm shift in leadership research. Leadership theories in this new paradigm differ from earlier theories in that they seek to explain extraordinary leadership and performance beyond expectations (Paul et al, 2002) This shift was catalyzed by the publication in 1978 of an influential book by Burns entitled "Leadership" which conceptualized the differences between ordinary (transactional) leaders and extraordinary (transformational) leaders (Barnett et al, 2001) Kouzes and Posner's model in transformational leadership The operationalization of the construct of leadership for this study is based on conceptualization of the Kouzes and Posner's leadership model. Their research, which they conducted over almost 20 years, suggested that leadership is not a position, but a collection of practices and behaviors.…”
Section: Theoretical Backgroundmentioning
confidence: 96%
“…Inconsistent findings and methodological problems resulting in increasing dissatisfaction with trait, behavioral, and contingency based leadership research had The case of Jordanian schools set the stage for a paradigm shift in leadership research. Leadership theories in this new paradigm differ from earlier theories in that they seek to explain extraordinary leadership and performance beyond expectations (Paul et al, 2002) This shift was catalyzed by the publication in 1978 of an influential book by Burns entitled "Leadership" which conceptualized the differences between ordinary (transactional) leaders and extraordinary (transformational) leaders (Barnett et al, 2001) Kouzes and Posner's model in transformational leadership The operationalization of the construct of leadership for this study is based on conceptualization of the Kouzes and Posner's leadership model. Their research, which they conducted over almost 20 years, suggested that leadership is not a position, but a collection of practices and behaviors.…”
Section: Theoretical Backgroundmentioning
confidence: 96%
“…According to theoretical and empirical research findings of several authors (Popper & Lipshitz, 2000;Politis, 2001;Sadler, 2001;Paul et al, 2002), one of the most appropriate leadership styles for knowledge organizations is the transformational leadership style. Transformational leaders are willing to sacrifice their individual interests for the good of the organization and its goals.…”
Section: Leadership For Kmmentioning
confidence: 98%
“…Transactional leaders do that by identifying the needs of followers and satisfying them when determined goals are achieved, whereas the self-management leadership style assists employees to develop an ability to manage themselves. In fact, in reality the leaders in organizations will probably exhibit a combination of these different styles in different contexts and, to a certain extent, adjusting them to each particular situation (Paul et al, 2002).…”
Section: Leadership For Kmmentioning
confidence: 99%
“…There are various school of thoughts for leaders and leadership (Park, 1997; Goleman, 2000; Politis, 2001; Bass et al , 2003; Culp and Smith, 2005) such as leadership style (employee‐oriented vs job‐centred; participative, self‐management and autocratic; close, general and laid‐back; transformational vs transactional; situational models and contingency approaches), leadership model (Sloan Leadership Model, CEL Leadership Framework), leadership index (Campbell Leadership Index and Myers Brigg Index) and theories of leadership (Trait theory, Blake and Mouton's Managerial Grid, Situational leadership theory, New Leadership Paradigm). In fact, in reality leaders in organisations will probably exhibit a combination of these different styles in different contexts and, to a certain extent, adjusting them to each particular situation (Paul et al , 2002). Figure 1 illustrates school of thought for leadership.…”
Section: Rationale For Leaders and Leadership For Six Sigma Initiativesmentioning
confidence: 99%